Mapping the Intellectual Landscape of Islamic Modernity: A Bibliometric and Critical Discourse Analysis of Global Scholarship - Saputra, Kurniawan Dwi; Utomo, Agus Himmawan (MUHARRIK: Jurnal Dakwah dan Sosial, 2025)
This research aims to explore the state of the art of Islamic modernity research using a VOSviewer bibliometric study. The research draws on the 5-year (2020-2025) SCOPUS database, utilizing the keyword "Islamic Modernity." The results were analyzed descriptively and put into a visualization. In each criterion, when possible, regional interpretations are presented to support further analysis. Afterwards, a cross-sectional critical discourse analysis is conducted heuristically. The findings indicate that the number of publications on "Islamic modernity" increases significantly from 2023 to 2024, and this trend continues into 2025. It also suggests that Islamic modernity discourse falls into two poles of intellectual motives: one, more epistemological in the form of theory construction, and the other, more political, as it pays more attention to political issues by scrutinizing the internal dynamics of Islamic society through a political interpretation. Thus, future research could contribute to critiquing the Eurocentric paradigm and foster epistemic justice in the global theory of knowledge.